Towards La Charte de l’Habitat: Jane Drew pioneering a ‘more humane architecture’ in Chandigarh - Nunes, Inês Leonor (2023)
In the post-war 1950s, the severe housing crisis triggered crucial reforms within the architectural field. The Modern Movement’s old guard, revisiting previous principles and tools, was questioned by an uprising avant-garde pursuing a more humane architecture. The C.I.A.M.s witnessed new paradigms towards housing and city, particularly the Aix-en-Provence Congress, entitled La Charte de l’Habitat. Despite this scission, bridges prevailed. Although being co-authored by the ‘elders’, Chandigarh’s masterplan, especially its inceptive Sector 22 layout, was planned by Jane Drew as a habitat. Containing the major daily programs, the coexistence of functions within the ecosystem challenged La Charte d’Athènes-based discourses. For the lowest ranks, Drew excelled, designing Peons’ Villages: humane microhabitats, communities combining housing, infrastructure, leisure, and green spaces near the collective equipment, transport, and communications networks serving Sector 22 macrohabitat. Indeed, notwithstanding a solid modernist affiliation, Drew was already pioneering a ground-breaking anthropological approach to design since working in West Africa. Attentive to the local culture and focused on future users’ practical needs and spiritual aspirations, Drew led participatory methodologies that superseded functionalism, notably preceding and framing later debates towards “habitat”. Based on the consultation of Drew’s unpublished archives and on my field trip to Chandigarh, I aim to highpoint Drew’s socially engaged discourses, suggesting her innovative contribution to a redirection within Modernism, framed by the discussion around the concept of “habitat”. The goal of the paper is to position a new light on Drew’s still-overlooked legacy, especially in her sensibly envisioned Chandigarh habitats, sharing how lively and preserved they are, seven decades later.